Simulation and Modeling Methodologies, Technologies and Applications : 8th International Conference, SIMULTECH 2018, Porto, Portugal, July 29-31, 2018, Revised selected papers /: 8th International Conference, SIMULTECH 2018, Porto, Portugal, July 29-31, 2018, Revised selected papers. (2020) - Unknown
No abstract available